Coexistence of sympatric yellow (Cynictis penicillatta) and slender (Galerella sanguinea) mongoose in an urban environment - Cronk, Nadine Elizabeth (My University, 2019)
Anthropogenic effects are driving extreme change in composition and structure of habitats at a global scale. Several wildlife species have been negatively impacted, yet other species are thriving in urban areas by exploiting anthropogenic habitats matching pre-existing niche preferences or modifying their biology for urban life. For species thriving in urban areas, food and shelter are potentially easily accessible and predation risk is reduced. Thus, urban areas might offer competing species similar opportunities to exploit the same resources, but the resources exploited might also be abundant enough to support large co-existing populations of these competing species. My study sought to determine the mechanisms of coexistence between the closely related and ecologically similar, yellow Cynictis penicillata and slender Galerella sanguineus mongoose. This was evaluated in two estates that varied slightly in their relative level of urbanisation, the Eco-Estate (more urbanised) and the Nature Estate (less urbanised), located in the south of Johannesburg, South Africa. I collected field data to assess diet, food selection, habitat preferences, activity patterns, and space use of each species, as well as the overlap in these biological parameters between the two species. Additionally, the home range of yellow mongoose was studied. First, scat analysis showed that: 1) insects and mammals were most abundant food item for both species in the Nature Estate and for slender mongoose in the Eco-Estate, while anthropogenic items were more prevalent than mammals for yellow mongoose in the Eco-Estate; 2) anthropogenic items were only prevalent in the more urbanised Eco-Estate; 3) scat components varied seasonally; and 4) dietary overlap was greatest in summer and lowest in winter. Second, food choice tests and carrion baited stations were used to establish food selection and feeding behaviour. I found that: 1) both species preferred meat and insects over other items, while yellow mongoose in the more urbanised estate preferred anthropogenic foods over insects; 2) yellow mongoose exhibited a shorter latency to approach and consume foods; and 3) slender mongoose were more prevalent at baited carcasses. Third, camera trap surveys established space use and activity patterns and showed that: 1) yellow mongoose were more prevalent in open habitats located near human residents, and slender mongoose were more common in covered areas further away from human residents, with spatial overlap being greater in a less urbanised estate; 2) species varied in peak active periods and overlap was greater in the more urbanised estate; and 3) complete spatio-temporal overlap was not apparent. Lastly, collaring and GPS tracking of the yellow mongoose showed that: 1) male home ranges were larger than that of females; 2) home range sizes in the less urbanised estate were larger; 3) home range sizes varied seasonally; and 4) home range overlap with human residents was greater in the more urbanised estate. In conclusion, I showed that urbanisation can have an effect on the resource use of the yellow and slender mongoose. Both species displayed similar characteristics of diet and space use to their non-urban counterparts. They varied in their use of different resources, and while they overlapped in some aspects, they differed in others, thereby permitting their coexistence in urban areas as presumably they would in non-urban areas. However, particularly in the yellow mongoose in the Eco-Estate, the exploitation of anthropogenic resources shows that they are also responding flexibly to urbanisation, and the differential use of these resources in urban areas further aids in their coexistence
Submitted in fulfillment of the requirements for the degree of Doctor of Philosophy in the Faculty of Science at the University of the Witwatersrand, Johannesburg May 2019